Protective effect of KCNH2 single nucleotide polymorphism K897T in LQTS families and identification of novel KCNQ1 and KCNH2 mutations - Oberti Carlos; Redfearn Sharon; Bryant Randall M; Liu Mugen; Zhang Li; Chen Shenghan; Zhang Xianqin; Vincent G Michael; Wang Qing K (BMC, 2008)
Abstract Background KCNQ1 and KCNH2 are the two most common potassium channel genes causing long QT syndrome (LQTS), an inherited cardiac arrhythmia featured by QT prolongation and increased risks of developing torsade de pointes and sudden death. To investigate the disease expressivity, this study aimed to identify mutations and common variants that can modify LQTS phenotype. Methods In this study, a cohort of 112 LQTS families were investigated. Among them two large LQTS families linkage analysis with markers spanning known LQTS genes was carried out to identify the specific gene for mutational analysis. All exons and exon-intron boundaries of KCNH2 and KCNQ1 were sequenced for mutational analysis. Results LQTS-associated mutations were identified in eight of 112 families. Two novel mutations, L187P in KCNQ1 and 2020insAG in KCNH2, were identified. Furthermore, in another LQTS family we found that KCNH2 mutation A490T co-segregated with a common SNP K897T in KCNH2. KCNH2 SNP K897T was reported to exert a modifying effect on QTc, but it remains controversial whether it confers a risk or protective effect. Notably, we have found that SNP K897T interacts with mutation A490T in cis orientation. Seven carriers for A490T and the minor allele T of SNP K897T showed shorter QTc and fewer symptoms than carriers with A490T or A490P (P < 0.0001). Conclusion Our family-based approach provides support that KCNH2 SNP K897T confers a protective effect on LQTS patients. Our study is the first to investigate the effect of SNP K897T on another KCNH2 mutation located in cis orientation. Together, our results expand the mutational and clinical spectrum of LQTS and provide insights into the factors that determine QT prolongation associated with increased risk of ventricular tachycardia and sudden death.